Study of nonlinear flow mechanisms and microfracture networks in low-permeability reservoirs - Hao, Mingqiang; Liu, Xuewei; Xia, Jing; Liu, Yang (Frontiers in Earth Science, 2023)
As efficient technologies boost oil yields and economic benefits, horizontal wells and hydraulic fracturing are widely used in low- permeability reservoirs. To better evaluate the reserve and improve recovery, it is essential to determine fluid flow patterns and transport mechanisms. Laboratory experiments, field operations, and analytical studies have identified nonlinear flow and microfracture networks during the fluid flow in a reservoir with fractured horizontal wells. However, the interactions between nonlinear flow and microfracture networks are still not fully understood. In this study, nonlinear flow experiments and triaxial compression tests were carried out to analyze nonlinear flow characteristics in the vicinity of microfracture networks. By analyzing the effects of microfracture networks on nonlinear flow, two-phase flow, rock stress sensitivity, and artificial fractures, we found that fluid capacity in capillaries with smaller dimensions decreased along with a drop in the pressure gradient, generating a nonlinear flow pattern. The area of nonlinear flow was diminished by the presence of microfractures, which improved flow efficiency and reservoir quality. Considering the size of fracture apertures, microfractures behave more like matrix pores than natural fractures. Also, microfractures significantly increase rock stress sensitivity and reduce the threshold permeability, which enhances fluid flow capacity. This study contributes to our understanding of flow behavior, predicting production and improving recovery in low-permeability reservoirs.